The Convergence of AI and animal-inspired robots for ecological conservation - Naqash Afzal; Mobeen ur Rehman; Lakmal Seneviratne; Irfan Hussain (Ecological Informatics)
Augmenting artificial intelligence through the integration of animal-inspired robots holds immense promise for transforming the landscape of ecological conservation. By harnessing the capabilities of AI-driven animal robots, researchers can gain a multifaceted toolkit to explore and understand the behaviors, communication patterns, and ecological roles of various species. These robotic counterparts could serve as invaluable proxies, allowing scientists to observe wildlife in their natural habitats without causing disturbance or altering their behaviors. Furthermore, this approach provides a novel means to study species that are difficult to observe directly, due to their elusive nature or the inaccessibility of their habitats.The collaborative interaction between AI and animal robots opens up avenues for the development of responsive and adaptable conservation strategies. AI algorithms deployed on interactive animal robots can continuously analyze real-time data from the field, allowing for dynamic adjustments in conservation approaches based on emerging patterns and threats. This agility is crucial in addressing the rapidly evolving challenges faced by the ecosystems and species in the wild. In this conceptual review, we discussed here, the opportunities for the fusion of artificial intelligence and animal-inspired robotics to revolutionize our ability to study wildlife and also empower us to implement more effective and sustainable conservation practices. This synergistic approach harnesses the strengths of both technology and biology, marking a significant leap forward in our efforts to protect and preserve the natural world.